Study on adaptive modulation in D2D communications over Nakagami-m fading channel - Xiaoping ZENG; Haiwei MAO; Fan YANG; Xin JIAN; Shiqi LI; Xin JIANG; Wei FANG (Tongxin xuebao)
A novel adaptive modulation based on nondata-aided error vector magnitude (NDA-EVM) was proposed to solve the problem of lower spectral efficiency in device to device (D2D) communication over Nakagami-m fading channel.The NDA-EVM was used to evaluate the channel quality.The relationship between NDA-EVM and symbol error ratio (SER) was derived according to the maximum likelihood method.Thereafter,the adaptive modulation mechanism of MQAM with the SER constraint was designed.Considering the joint effect of finite-length queuing and fading channel,the system packet loss rate and spectral efficiency was analyzed.Theoretical analysis and simulation experiments show that NDA-EVM based adaptive modulation accurately gives the modulation threshold and evaluates the relationship between QoS and packet loss rate,the proposed algorithm improves system spectral efficiency while maintaining low algorithm complexity,spectral efficiency improves by 0.752 bit·(s·Hz)-1,compared with traditional algorithm.